Understanding editorial independence and public accountability issues in public broadcasting service: a study of the editorial policies at the South African Broadcasting Corporation (SABC) - Jjuuko, Denis Charles (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2005)
The concepts of editorial independence and public accountability are necessary in public broadcasting service as they help make a distinction between a public service broadcaster, a government and a commercial service broadcaster. This is because public service broadcasters are tasked with the responsibility of serving the interests of the general public. To do this, the above mentioned concepts have to be in place. This study examines these issues (editorial independence and public accountability) with reference to a case study of the editorial policies of the South African Broadcasting Corporation (SABC). Using public broadcasting theory, policy theory and qualitative research methods, the study examines the genesis of these editorial policies in 2003/2004 and how they provide the SABC with a means of balancing the tensions of editorial independence and public accountability. In analysing the SABC's editorial policies, the study deals only with those policies whose principles are directly related to editorial independence and public accountability. Although some of these policies are found to be in line with public broadcasting service trends, others are found lacking. Various recommendations are made. The case study demonstrates the importance of an integrated and elaborated policy perspective in setting out how a public service broadcaster can manage editorial independence and public accountability. It also highlights the importance of using international 'role models' in ways that are appropriately adapted for the specific country concerned.
Keywords: South African Broadcasting Corporation; South African Broadcasting Corporation -- Law and legislation; Broadcasting -- Social aspects -- South Africa; Mass media -- Social aspects -- South Africa; Broadcasting policy -- South Africa